A subset of AID‐dependent B‐1a cells initiates hypersensitivity and pneumococcal pneumonia resistance. Issue 1 (10th December 2015) - Askenase, Phillip W.; Bryniarski, Krzysztof; Paliwal, Vipin; Redegeld, Frank; Groot Kormelink, Thomas; Kerfoot, Steven; Hutchinson, Andrew T.; van Loveren, Henk; Campos, Regis; Itakura, Atsuko; Majewska‐Szczepanik, Monika; Yamamoto, Natsuo; et al.
Abstract : We propose that there is a special B‐1a B cell subset ("sB‐1a" cells) that mediates linked processes very early after immunization to initiate cutaneous contact sensitivity (CS), delayed‐type hypersensitivity (DTH), and immune resistance to pneumococcal pneumonia. Our published data indicate that in CS and DTH, these initiating processes are required for elicitation of the delayed onset and late‐occurring classical T cell–mediated responses. sB‐1a cells resemble memory B2 cells, as they are stimulated within 1 h of immunization and depend on T helper cytokines—uniquely IL‐4 from hepatic iNKT cells—for activation and rapid migration from the peritoneal cavity to the spleen to secrete IgM antibody (Ab) and Ab‐derived free light chains (FLCs) by only 1 day after immunization. Unlike conventional B‐1a (cB‐1a) cell–produced IgM natural Ab, IgM Ab produced by sB‐1a cells has high Ag affinity owing to immunoglobulin V‐region mutations induced by activation‐induced cytidine deaminase (AID). The dominant cB‐1a cells are increased in immunized AID‐deficient mice but do not mediate initiation, CS, or pneumonia resistance because natural Ab has relatively low Ag affinity because of unmutated germ‐line V regions. In CS and DTH, sB‐1a IgM Ag affinity is sufficiently high to mediate complement activation for generation of C5a that, together with vasoactive mediators such as TNF‐α released by FLC‐sensitized mast cells, activate local endothelium for extravascular recruitment of effector T cells. We conclude by discussing the possibility of functional sB‐1 cells in humans.